EVALUATION OF EGG REPLACERS IN A YELLOW CAKE SYSTEM - Kohrs, D.; Herald, . J.; Aramouni, F. M.; Abughoush, M. (Emirates Journal of Food and Agriculture, 2017)
The egg alternatives (replacers) were used to replace egg as a functional ingredient in yellow cake system productions. Egg replacers were substituted at the levels of 50% and 100% of the dried whole eggs in the yellow cake system. The egg replacers were composed of whey protein isolate, wheat starch, guar gum, xanthan gum or their blends. At 50% substitution, treatments performed closer to that of control compared to 100 % substitution. The blends of guar/whey/starch (GPS) and xanthan/whey/starch (XPS) performed the best, having the closest volume and texture measurement compared to the control. A quantitative descriptive analysis (QDA) was performed on blends of GPS and XPS at 100% replacement. Six attributes of cakecrust stickiness, crumb color, springiness, moistness, firmness, and egg flavor–were quantified by a panel. These treatments were competitive to the control across all attributes measured. In the consumer acceptability test, the XPS formulation was significantly higher in acceptability for all attributes to that of the control. These alternatives can deliver functionality at a lower cost and can be incorporated to produce a suitable yellow cake system, especially blends of guar/whey/starch (GPS) and xanthan/whey/starch (XPS). These results may help producers in formulating yellow cake system.